Naomi Osaka : her journey to finding her power and her voice - Rothenberg, Ben (Dutton, an imprint of Penguin Random House LLC, 2024)
"A deeply reported, revealing biography of tennis phenomenon and activist Naomi Osaka, telling the untold story behind her Grand Slam-winning career, her headline-making advocacy for racial justice and mental health, and the challenges of a life in the international spotlight"--